Pola Kerukunan Antarumat Islam dan Hindu di Denpasar Bali - Kunawi Basyir (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2013)
This study attempts to review the religious life of multicultural society of Muslim-Hindus in Denpasar, Bali. Findings of the fieldwork reveal the prevalence of an ideal cooperation among religous communities in building harmony in religious life. This character constitutes an integral part of Balinese societal life. Building Bali Aga (Bali Sprouts Again) needs a long process and time through theological, ideological and socio-cultural dialectics. The local government and social institutions together with Balinese society have been struggling to maintain and protect the Hindu-inspired Balinese culture through preserving the tradition of menyama braya to establish a harmonious religious life. They also exhibit inclusive religiousity in social, cultural, economic, and educational spheres. It is with this openness that Muslim-Hindu community in Bali can live in a peaceful co-exisentence and respect each other.